THE ASSESSMENT OF COMPATIBILITY OF WASTEWATER TREATED BY NATURAL LAGOON WITH DISCHARGE AND IRRIGATION STANDARDS. CASE STUDY - M., Djaani1*; Z., Baba amer2 (university of eloued جامعة الوادي, 2020)
In order to protect the environment and the groundwater against pollution, we dealt with one of the problems in the world, regarding the treatment of wastewater and the possibility of reuse with irrigation. We studied the case of the Kef Eddouken natural lagoon treatment plant in Ghardaia (southern Algeria). For this reason we studied the physico-chemical, bacteriological and parsitological parameter of waste and treated water. The results of the analysis show that all the previous parameters comply with the Algerian standard of rejection except electrical conductivity, suspended matter and BOD5. On the other hand, despite the electrical conductivity exceeds the limit, but it corresponds to the SAR value; according to the Algerian and the international standard of irrigation, this quality of water can be used sub-irrigation for vegetable which eaten only cooked.
artical
Keywords: Waste water; treated water; environment; groundwater; irrigation; Kef Eddouken WWTP